The Effect of Adiantum Capillus-veneris L. Hydroalcoholic Extract on the Oxidative Stress Rate of Mice's Blood and Brain in the Depression Model Caused by Acute Immobilization Stress - Jafar Ahmadpouri; Saeid Valipour Chahardahcharic; Mahbubeh Setorki (Mazandaran University of Medical Sciences, 2020)
Background: The oxidant-antioxidants balance in the living organism is constantly challenged by internal and external pressures. Maidenhair or Adiantum capillus-veneris (Acv) is rich in bioactive compounds with antioxidant effects.  Objectives: The present study aimed at investigating the effect of Acv hydroalcoholic extract on the oxidative stress rate of blood and brain of mice in the depression model caused by acute immobilization stress. Methods: In this study, 40 male Balb/C mice were randomly divided into five groups, including 1 (control, 2, 3, and 4) intervention (receiving doses of 100, 200, and 400 Acv extracts) and diazepam group. Acute stress was induced by motion limitation (2 hours) and electrochemical shock (0.5 mA, 2 min), and then the mice were treated intraperitoneally with the extract or drug for 21 days. First, the rate of depression was assessed by forced swimming. Then, the Total Antioxidant Capacity (TAC), serum Malondialdehyde (MDA), and the MDA level of the brain were determined. Results: The prescription of different doses of Acv extract and diazepam significantly reduced the duration of immobilization in the forced swimming test compared with the control group (P<0.05). Besides, Acv extract at different doses of  200 and 400 significantly increased serum FRAP (TAC) and significantly increased TAC of the brain compared with the control group. Administration of Acv extract at different doses of 200 and 400  and diazepam significantly decreased serum MDA but significantly decreased MDA of the brain of mice compared with the control group (P<0.05). Conclusion: Acv extract can reduce the symptoms of depression and protect against acute stress-related oxidative stressors